Multidimensional evaluation of peripubertal swimmers: Multiple regression analysis applied to talent selection - Saavedra, J.; Escalante, Y.; Rodriguez, F. (Biomechanics and Medicine in Swimming IX, 2003)
INTRODUCTION The aim of this investigation was to analyse different somatic, physical fitness, technical and performance characteristics of peripubertal swimmers from a multidimensional perspective, to obtain statistically developed reference norms for various testing procedures, and to build multivariate models for performance prediction (Solanellas & Rodríguez 1996). METHODS 133 young swimmers, 66 males (age 13.6±0.56 y) and 67 females (11.51±0,55 y) selected among the best national swimmers by the Spanish federation (R.F.E.N.) participated in the study. All subjects undertook the META-NAT test battery (Saavedra et al., unpublished), including: 1) sports background and training status questionnaire; 2) somatic evaluation (body composition, somatotype, and sexual maturation rating); 3) general fitness tests (including the Eurofit test battery); 4) specific swimming and pool tests (Vcrit, 30 min test, 6x50 m, 10 m maximal test, sliding and floating tests among others); and 5) technical analysis (Arellano 1993). Multiple linear regression (MLR) models were developed (stepwise selection), with competitive performance (L.E.N. scores in 3 best events) as the predicted variable. DISCUSSION Both models included age, as well as aerobic and mixed endurance indicators. These results suggest that swimming competitive performance can be predicted from a few somatic, fitness, and technical parameters in young peripubertal swimmers. This multidimensional valuation procedure can be applied to talent selection and development in younger swimmers.